Sustainability training at Spanish public faculties of education: a virtual ethnography - Antonio Nadal Masegosa; Lucía Rodríguez-Olay (Tópicos Educacionais)
Various institutional statements and official documents refer to the Sustainable Development Goals and sustainability training. This should imply a university education in these values, considering that those who are going to train the new generations, in the Spanish State, must pass through the faculties of education. Through an investigation developed thanks to the methodology and design of virtual ethnography, the web pages of all the Spanish public faculties of education were analyzed, managing to find few training options during the initial period of the 2020/2021 academic year, specifically during the months of September and October, in a reality that reflects deficiencies that should be corrected immediately. Education for sustainability cannot be a priority in the 2030 Agenda and yet, in future education professionals, remain in a declaration of intentions, or something that implies little more than some isolated training course, and the results of the research show that the object of study barely manages to be found in the training offered. In the same way, being able to find training for education in sustainability should not involve an arduous research within the official websites, since this would not reflect a priority approach on the part of the institutions.